AB1129 PREVALENCE OF FINDINGS IN ROUTINE ABDOMINAL ULTRASOUND IN PATIENTS WITH CONNECTIVE TISSUE DISEASES AND THEIR IMPACT ON DISEASE MANAGEMENT. (2nd June 2020) - Weiß, K.; Schmidt, W. A.; Krause, A.; Schäfer, V. S.
Abstract : Background: Patients with connective tissue diseases (CTD) are often screened for abdominal organ involvement with ultrasound. Objectives: To analyse the prevalence of routine abdominal ultrasound findings in different CTD entities and their impact on therapeutic decisions. Methods: Retrospective chart review of all in-patients from a tertiary rheumatological referral center with CTD diagnosis and abdominal ultrasound examination between January 1st 2006 and December 31st 2015. Descriptive statistics were used to describe patient characteristics and frequencies of ultrasound findings. To determine whether findings impacted therapeutic decisions, we analysed if they were discussed in the hospital discharge letter. Results: 1.092 patients with a total of 1.695 hospitalizations were analysed. Mean age was 55.1 years (range: 17-90 years, SD: 15.8), mean disease duration was 6.4 years (range: 0.0-52.8 years, SD: 9.1). 87.5 % were female. Table 1 shows the frequency of findings per CTD entity. 48 out of all 1.695 examinations were discussed in the hospital discharge letter. In 30 cases, the physician described the ultrasound results as pivotal for therapeutic decision-making. Conclusion: Routinely performed abdominal ultrasound rarely yields disease specific findings which subsequently impact the therapeutic decision-making process. Disclosure of Interests: None declared